One clear objective poverty reduction through sustainable development - Committee to Review the Australian Overseas Aid Program; Simons, H. Paul.; Australian Agency for International Development (Canberra Australian Agency for International Development, 1997)
Australia's official overseas aid program involves expenditure of well over one billion dollars every year. While this is a modest contribution, both in terms of global aid funds and Australian government outlays, it is still a significant use of taxpayers' funds. It is against this background that the Review Committee reported to the Minister for Foreign Affairs on how the Australian overseas aid program can best contribute to lasting poverty reduction, while also serving Australia's interests. They also reported on the overall priorities, objectives and focus for the program. The Review found that the program suffered from the lack of a clear objective, leaving it open to being pulled in different directions. The aid program is also in need of renewal, not just to accommodate the rapidly changing international environment, but also to shake out the habitual, to inject greater vitality and rigour and to sharpen the focus on the pursuit of excellence.
H. Paul Simons, chairman.
"April 1997"
"The Australian Overseas Aid Program"--t.p.
Bibliography: p. 323-328.
Tac-3632g donated by Read World Foundation on 25 June 2015.
Keywords: Australian Overseas Aid Program; Australian Agency for International Development; Economic assistance, Australian -- Developing countries; Economic assistance -- Government policy -- Australia